The state debt of the Russian Federation, the constituent entities of the Russian Federation and municipalities - N. Z. Zotikov; A. F. Savderova (Вестник университета, 2021)
The state debt is the obligations of the constituent entities of the Russian Federation arising from the state loans assumed by the Russian Federation, guarantees for the obligations to repay in the same amount with the payment of additional interest for the use of the loan. The issue of state and municipal debt and the resulting need for regional and municipal borrowing are particularly relevant for the constituent entities of the Russian Federation and municipalities, since the current fiscal mechanism does not actually provide the principle of independence and balance of budgets,according to which the amount of budget expenditures should correspond to the total amount of budget revenues. According to the authors, the lack of funds is caused not only by the budget deficit, but to a greater extent by the shortcomings of the existing fiscal mechanism. The relationship between the budget deficit and the state debt is manifested in the subsequent increase in debt obligations due to the need to repay the debt and interest for using it. The purpose of the article is to assess the debt burden at the level of the state, constituent entities and municipalities in the current economic conditions, the impact of the revenues of the respective budgets on it.